2020
DOI: 10.3390/ijms21249658
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate Attenuates Lung Inflammation and Oxidative Stress Induced by Chronic Exposure to Diesel Exhaust Particles in Mice

Abstract: Air pollution is mainly caused by burning of fossil fuels, such as diesel, and is associated with increased morbidity and mortality due to adverse health effects induced by inflammation and oxidative stress. Dimethyl fumarate (DMF) is a fumaric acid ester and acts as an antioxidant and anti-inflammatory agent. We investigated the potential therapeutic effects of DMF on pulmonary damage caused by chronic exposure to diesel exhaust particles (DEPs). Mice were challenged with DEPs (30 μg per mice) by intranasal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Clinical evidences demonstrated the superiority of DMF in treating multiple sclerosis patients and preclinical studies have shown that DMF could treat several human diseases including lung disease. Cattani-Cavalieri et al found that DMF could attenuate lung injury induced by chronic exposure to diesel exhaust particles in mice [23]. Grzegorzewska et al reported that DMF ameliorates pulmonary arterial hypertension and bleomycin-induced lung brosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidences demonstrated the superiority of DMF in treating multiple sclerosis patients and preclinical studies have shown that DMF could treat several human diseases including lung disease. Cattani-Cavalieri et al found that DMF could attenuate lung injury induced by chronic exposure to diesel exhaust particles in mice [23]. Grzegorzewska et al reported that DMF ameliorates pulmonary arterial hypertension and bleomycin-induced lung brosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation and nitration of manganese-superoxide dismutase (MnSOD) are present in the asthmatic airways, and these modifications correlate with clinical features of asthma severity. Tyrosine nitration and chlorination from eosinophil and neutrophil activation cause inhibition of MnSOD activity and catalase, impairing antioxidant defenses in asthma [ 72 , 80 , 81 , 82 , 83 , 84 ]. Redox imbalance and redox-dependent mechanisms engage inflammatory mediator release, epithelial damage, reduced lung function and airway hyperresponsiveness in asthma pathogenesis [ 85 , 86 ].…”
Section: Oxidative Stress In Asthmamentioning
confidence: 99%
“…Secondly, DEP is also known for its induction of oxidative stress and DNA damage in the airways via ROS [147][148][149][150][151][152]. H 2 O 2 , a marker for oxidative stress, is increased in BAL fluid of mice exposed to DEP together with serum ceramide levels clearly indicating that oxidative stress is induced after DEP exposure [147,149].…”
Section: Diesel Exhaust Particlesmentioning
confidence: 99%